2016
DOI: 10.1136/bjophthalmol-2016-308769
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus in children with white matter damage of immaturity: MRI correlation

Abstract: The prevalence of strabismus increased with the severity of WMDI and was higher among patients with WMDI than among healthy individuals. The severity of WMDI might be related to the presence and constancy of strabismus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…24,25 It has been reported that exotropia or esotropia are common in children with PVL, and the prevalence increases with the severity of white matter damage. 26 However, esotropia is more common in children who do not develop cerebral palsy. 27 In cases of early-onset esotropia, white matter lesions may only be seen as periventricular signal changes in MRI or may not be detected at all.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 It has been reported that exotropia or esotropia are common in children with PVL, and the prevalence increases with the severity of white matter damage. 26 However, esotropia is more common in children who do not develop cerebral palsy. 27 In cases of early-onset esotropia, white matter lesions may only be seen as periventricular signal changes in MRI or may not be detected at all.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha señalado a la inmadurez como uno de los factores causales del estrabismo 2,18 , sin embargo, un asunto es señalar a la inmadurez como una causa vinculada al origen del EC, y otra, establecer con absoluta precisión el grado de inmadurez requerido para que el EC se manifieste en sus variadas formas de presentación.…”
Section: Discussionunclassified
“…Para inquirir respecto a las implicaciones que representa la inmadurez cortical, se decidió aplicar la presente metodología al EC, por considerarlo como un modelo biológico con alteraciones corticales ya demostradas 1,4,18 , que resulta sencillo de explorar, calificar y cuantificar de manera precisa en cada una de sus manifestaciones sensoriales y motoras.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Strabismus is associated with neurodevelopmental and neurologic disorders such as cerebral palsy [58][59][60], Down's syndrome [61][62][63], neurodevelopment delay [61,63,64], intellectual disability [65], and white matter damage of immaturity [66]. Greenberg investigated the prevalence and types of esotropia in a Western population and found that 11.4% of esotropias were associated with CNS defects: cerebral palsy, developmental delay, Down syndrome, and seizure disorder [4].…”
Section: Strabismus Of Central Originmentioning
confidence: 99%